Learning Styles and Learning Preferences (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the concept of learning styles and learning preferences, providing an overview of different learning theories, models, and the relevance of these concepts in education. The aim is to understand how individual differences in learning can impact educational outcomes and how teachers and educators can adapt their teaching strategies to accommodate diverse learners. The article also includes a review of existing literature on learning styles, methodology used to analyze these styles, and the findings from the research.